Potential geographical distribution of Garcinia paucinervis Chun et How in China under future climate change scenarios based on the MaxEnt Model - Hongqun Li; Lei Cheng; Junfang Song; Xieping Sun (PLoS ONE, 2025)
Garcinia paucinervis Chun et How is a tree species with important ecological, medicinal, and ornamental value. Studying the impact of climate change on the potential distribution of this species offers important information for resource conservation, population restoration, and sustainability. In this study, the MaxEnt model was used to simulate potential distributions under climate change conditions. Results showed that the precipitation of the driest quarter (Bio-17) ranging from 33.3 to 133.3 mm, the precipitation of the warmest quarter (Bio-18) from 667.67 to 1000 mm, the annual mean temperature (Bio-01) from 18.0 to 24.0 °C, and the annual precipitation (Bio-12) from 1250.0 to 1760.0 mm were four dominant factors affecting the distribution of G. paucinervis. Its suitable habitat in China is the narrowest, and it is located in most regions of Guangxi and Guangdong, the southern region of Guizhou, and the southeastern part of Yunnan Province. In the 2050s and 2070s, the geographical distribution gradually decreased compared to current scenarios. Specifically, most of Guangxi and Guangdong, the southern region of Guizhou, the eastern part of Yunnan adjacent to Guangxi, the southeast region of Sichuan, and the northern region of Hainan were identified as stable suitable habitats for G. paucinervis. Meanwhile, the expanding areas were located only in the western and southern regions of Yunnan, and the contracting areas were in the junction of Guangdong, Fujian, and Jiangxi; among Guizhou, Chongqing, and Hunan; among Anhui, Henan, and Hubei; the southeastern region of Sichuan; the western region of Hubei; and the adjacent area between Chongqing and Sichuan. By the 2070s, the contracting habitats will additionally include the central Guizhou region, the northern regions of Guangdong and Guangxi, the eastern region of Guangdong adjacent to Fujian, and the southern Jiangxi Provinces. Thus, this study highlights the vulnerability of the species and its response to future climate change and provides insights for assessing habitat suitability for conservation management.